Physical, language, neurodevelopment and phenotype-genotype correlation of Chinese patients with Mowat-Wilson syndrome - Wu, Lihua; Wang, Jianhong; Wang, Lei; Xu, Qi; Zhou, Bo; Zhang, Zhen; Li, Qi; Wang, Hui; Han, Lu; Jiang, Qian; Wang, Lin (Frontiers in Genetics, 2022)
Background: To report detailed knowledge about the clinical manifestations, genetic spectrum as well as physical, language, neurodevelopment features and genotype-phenotype correlations of Chinese patients with Mowat-Wilson syndrome (MWS). Methods: We retrospectively collected and analyzed clinical data for twenty-two patients with molecularly confirmed diagnoses. We used Gesell Developmental Schedules (GDS) to assess their neurodevelopment and the Diagnostic Receptive and Expressive Assessment of Mandarin-Infant & Toddler (DREAM-IT) to evaluate their language ability and compared the data with the two types of underlying pathogenic variations. Results: The height and weight of all patients were below the 75th percentile, and microcephaly was observed in 16 of 22 patients (72.7%). Four patients carrying chromosome deletions encompassing the ZEB2 gene were more severely affected. All MWS patients exhibited better performance in cognitive play and social communication than in receptive and expressive language. In the receptive language area, the types of words that children with MWS understood most were nouns, followed by adjectives and verbs. Conclusion: This study delineated the phenotypic spectrum of the largest MWS cohort in China and provided comprehensive profiling of their physical, language, neurodevelopment features and genotype-phenotype correlations.